Joint meeting of I.F.T.U. Executive and L.S.I. Bureau, held in C.G.T. offices, Paris, on September, 13,15 and 16, 1937 (draft report) - International Federation of Trade Unions ; Labour and Socialist International
1937-09-21 016b-0051-004 292/946/16b/55(iv)